Regulating Private Tutoring in China: Uniform Policies, Diverse Responses. (March 2019) - Zhang, Wei
Purpose: This article examines responses from the tutoring sector to Chinese national and local government regulations on private supplementary tutoring. It adds to the literature on policy enactment, showing the importance of context and noting the diversity of tutoring providers compared with schools. Design/Approach/Methods: The article draws on semi-structured and informal interviews with 11 tutors, 15 managers of tutoring enterprises, 5 members and managers of professional organizations, 5 government officials, 5 school managers, 5 teachers, and 20 parents. Data from interviewees were triangulated with observations, news reports, blogs written by tutoring analysts, and ad hoc research by industrial observers. Findings: Policy enactment in the tutoring sector is even more complex than that for schooling. Standardized policies do not necessarily achieve the aspired goals. Originality/Value: The article adds to the literature not only in China but also internationally. It highlights the importance of distinguishing between aspirations and realities in this domain. It also proposes conceptual considerations for regulating tutoring, given its diverse and fluid nature.